PENGARUH TERAPI SLOW DEEP BREATHING KOMBINASI DZIKIR ASMAUL HUSNA TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI DESA AMBULU PROBOLINGGO - Darul Alam Bil Gisti; Ro’isah Ro’isah; Erna Handayani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Hypertension is a problem that needs to be watched out for, because there are no signs of specific symptoms in hypertension and some people still feel healthy to do their usual activities. This is what makes hypertension a silent killer. The purpose of this study is to determine the effect of Slow Deep Breathing therapy in combination with Dhikr Asmaul Husna on changes in blood pressure in Hypertension patients in Ambulu Probolinggo.This research is pre-experimental with a one-group pre test and post test design. The population of 37 people with hypertension with a sampling technique using purposive sampling, namely 34 respondents with hypertension who have inclusion and exclusion criteria. Data collection was conducted using a Ratio scale observation sheet. The statistical test uses the Wilcoxon test.Results of the study were obtained by respondents before the Slow Deep Breathing therapy in combination with Dhikr Asmaul Husna was obtained as the most Grade 2 Blood Pressure Change value, namely 23 respondents (67.6%), and the value after Slow Deep Breathing therapy in combination with Dhikr Asmaul Husna was obtained the most Blood Pressure Change value classified as Degree 1, namely 25 respondents (73.5%), From the results of the Wilcoxon statistical test, p value = 0.001 was obtained. This shows that Slow Deep Breathing therapy in combination with Dhikr Asmaul Husna affects changed in blood pressure in people with hypertension.Slow Deep Breathing Therapy in combination with Dhikr Asmaul Husna is a program that can be applied to Hypertension patients who have High Blood Pressure. nurses are expected to be able to use Slow Deep Breathing Therapy in combination with Dhikr Asmaul Husna as a health promotion program.